2006
DOI: 10.1021/ac052085y
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Extraction and Elution on Diamond (SPEED):  A Fast and General Platform for Proteome Analysis with Mass Spectrometry

Abstract: This paper presents a new solid-phase extraction and elution platform based on surface-functionalized diamond nanocrystallites. Compared with conventional methods, the platform facilitates purification and concentration of intact proteins and their enzymatic digests for ensuing sodium dodecyl sulfate-polyacrylamide gel electrophoresis or matrix-assisted laser desorption/ionization mass spectrometry analysis without prior removal of the adsorbent. One-pot work flow involving reduction of disulfide bonds, protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 29 publications
3
70
0
Order By: Relevance
“…Carbon exists in a number of allotropic forms, such as fullerenes, CNTs, including single-walled CNTs (SWCNTs) and multi-wall CNTs (MWCNTs), carbon nanohorns, carbon nanocones, carbon nanodisks, carbon nanofibers, nanotube rings, graphene oxide (GO) and graphene (G), and diamonds [22][23][24][25][26]. However, to date, from the analytical point of view, the applications have mainly been focused on the use of fullerenes, CNTs and GO/G.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…Carbon exists in a number of allotropic forms, such as fullerenes, CNTs, including single-walled CNTs (SWCNTs) and multi-wall CNTs (MWCNTs), carbon nanohorns, carbon nanocones, carbon nanodisks, carbon nanofibers, nanotube rings, graphene oxide (GO) and graphene (G), and diamonds [22][23][24][25][26]. However, to date, from the analytical point of view, the applications have mainly been focused on the use of fullerenes, CNTs and GO/G.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…Digestion of MPs was implemented according to the measures of an earlier publication with some changes on the surface of the AF-Tresyl-650M material [28]. MPs was dissolved with 4% SDS, which was carried out at À20 C using sonication in water bath for 20 min.…”
Section: Membrane Proteins Enrichment and Digestion With Af-tresyl-65mentioning
confidence: 99%
“…Compared with direct MALDI MS analysis, the detection sensitivity has been enhanced by more than 2 orders of magnitude using this pre-concentration strategy. The authors further demonstrated that these surface-functionalized nanodiamonds could also be used to extract protein digests from dilute solutions containing high concentrations of urea, salts, and detergents [59]. Wei et al found that detonation nanodiamond (dND) could be used as adsorbent for pretreatment of peptides in dilute/contaminated sample solutions [60].…”
Section: Enrichment Of Low-abundance Peptides/proteinsmentioning
confidence: 99%